A Systematic Literature Review on Social Media Marketing in Small and Medium Enterprises. Issue 1 (March 2023) - Kanth, Grishma; Prasad, R. Siva Rama
This article intends to systematically examine and review the current studies on social media marketing in the small and medium enterprise sector. The research also intends to synthesise and organise the unique aspects covered in these studies and further understand how these various issues related to social media marketing were addressed in these studies. The review covers 48 articles, collected from peer-reviewed journals from 2009 to 2019. These articles are then classified in different categories based on the central theme of research, research design of the study, theoretical model used in the study, country of study and social media platform used in the research. The findings of the review provide an overview of the categories as well as the most widely used subcategory for each classification, along with upcoming trends and tendencies in social media marketing.